(untitled) (African Journal of Biomedical Research, 2020)
Nuclear-encoded transcriptional regulatory proteins called transcription factors can potentially influence mitochondrial gene expression directly or indirectly. Mitochondria contain their own genome, which encodes 13 of the ∼100 proteins that constitute the enzyme complexes of the respiratory chain. Mitochondria are the fuel stations of all eukaryotic cells and functions as central component of mammalian cellular survival through production of ATP and re-oxidized NAD. Nuclear respiratory factor-1 (NRF- 1) coordinates the expression of nuclear and mitochondrial genes for mitochondrial biogenesis. It increases mitochondrial respiratory capacity and induces expression of a subset of genes governing mitochondrial activity. It has a major function in cellular adaptation to energy demands by translating physiological signals into an enhanced capacity for energy production. Oxidative stress has been implicated in the pathogenesis of many diseases such as diabetes, cardiovascular disease, cancer and neurodegenerative diseases. NRF proteins are also essential in the upregulation of antioxidant and xenobiotic-metabolizing enzymes during oxidative stress. NRF-1 plays a role in mediating activation of oxidative stress response genes through antioxidant response element and hence, confirms its potential roles in chronic diseases. This review has clearly revealed the versatility of NRF- 1 as a therapeutic target and showed that plants could exhibit their fight against diseases through activation of NRF-1.